2019
DOI: 10.1186/s12882-019-1304-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported advantages and disadvantages of peritoneal dialysis: results from the PDOPPS

Abstract: Background Patient-reported measures are increasingly recognized as important predictors of clinical outcomes in peritoneal dialysis (PD). We sought to understand associations between patient-reported perceptions of the advantages and disadvantages of PD and clinical outcomes. Methods In this cohort study, 2760 PD patients in the Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS) completed a questionnaire on their PD experience, between 2014 and 2017. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Nevertheless, as PD is a home dialysis treatment that requires patients to participate and contribute, it is beneficial if patients’ personalities make them suited to the treatment. Besides patients’ personal conditions like poor mobility, comorbidities [ 38 ], a lack of space for PD supplies at home [ 39 ] or the involvement of partners [ 40 ], nephrologists should be aware of taking patients’ personality into account to get an idea whether PD could be an option for them. A review of the barriers in dialysis modality choice showed that pre-dialysis education programs and decision aids can help to enable patients to make an autonomous and confident decision when selecting a dialysis modality [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as PD is a home dialysis treatment that requires patients to participate and contribute, it is beneficial if patients’ personalities make them suited to the treatment. Besides patients’ personal conditions like poor mobility, comorbidities [ 38 ], a lack of space for PD supplies at home [ 39 ] or the involvement of partners [ 40 ], nephrologists should be aware of taking patients’ personality into account to get an idea whether PD could be an option for them. A review of the barriers in dialysis modality choice showed that pre-dialysis education programs and decision aids can help to enable patients to make an autonomous and confident decision when selecting a dialysis modality [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Indeed, data from the Peritoneal Dialysis and Practice Patterns Study (PDOPPS) has shown patients who have a negative perception of PD modality tend to have lower HRQOL and are under a greater risk of technique failure over time. [23] We hypothesize fatigue symptoms at the transition phase to PD for kidney replacement therapy may disproportionally affect home-therapy patients, as a successful transition to dialysis requires greater patient engagement.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“… 55 The Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS) of over 2,700 patients undergoing PD also revealed that individuals most frequently viewed receiving treatment at home and not requiring blood access as the major advantages of PD, while feeling abdominal fullness or bloating, having their home space taken up by PD supplies, and the impact or burden on family were the most severe disadvantages. 56 These perceived disadvantages were associated with a higher likelihood of transition to HD, lower HRQoL, and higher depression scores.…”
Section: What Are Pd Patients’ Priorities?mentioning
confidence: 99%